Spaces:
Sleeping
Sleeping
.. Copyright (C) 2001-2023 NLTK Project | |
.. For license information, see LICENSE.TXT | |
============================================================================== | |
Glue Semantics | |
============================================================================== | |
====================== | |
Linear logic | |
====================== | |
>>> from nltk.sem import logic | |
>>> from nltk.sem.glue import * | |
>>> from nltk.sem.linearlogic import * | |
>>> from nltk.sem.linearlogic import Expression | |
>>> read_expr = Expression.fromstring | |
Parser | |
>>> print(read_expr(r'f')) | |
f | |
>>> print(read_expr(r'(g -o f)')) | |
(g -o f) | |
>>> print(read_expr(r'(g -o (h -o f))')) | |
(g -o (h -o f)) | |
>>> print(read_expr(r'((g -o G) -o G)')) | |
((g -o G) -o G) | |
>>> print(read_expr(r'(g -o f)(g)')) | |
(g -o f)(g) | |
>>> print(read_expr(r'((g -o G) -o G)((g -o f))')) | |
((g -o G) -o G)((g -o f)) | |
Simplify | |
>>> print(read_expr(r'f').simplify()) | |
f | |
>>> print(read_expr(r'(g -o f)').simplify()) | |
(g -o f) | |
>>> print(read_expr(r'((g -o G) -o G)').simplify()) | |
((g -o G) -o G) | |
>>> print(read_expr(r'(g -o f)(g)').simplify()) | |
f | |
>>> try: read_expr(r'(g -o f)(f)').simplify() | |
... except LinearLogicApplicationException as e: print(e) | |
... | |
Cannot apply (g -o f) to f. Cannot unify g with f given {} | |
>>> print(read_expr(r'(G -o f)(g)').simplify()) | |
f | |
>>> print(read_expr(r'((g -o G) -o G)((g -o f))').simplify()) | |
f | |
Test BindingDict | |
>>> h = ConstantExpression('h') | |
>>> g = ConstantExpression('g') | |
>>> f = ConstantExpression('f') | |
>>> H = VariableExpression('H') | |
>>> G = VariableExpression('G') | |
>>> F = VariableExpression('F') | |
>>> d1 = BindingDict({H: h}) | |
>>> d2 = BindingDict({F: f, G: F}) | |
>>> d12 = d1 + d2 | |
>>> all12 = ['%s: %s' % (v, d12[v]) for v in d12.d] | |
>>> all12.sort() | |
>>> print(all12) | |
['F: f', 'G: f', 'H: h'] | |
>>> BindingDict([(F,f),(G,g),(H,h)]) == BindingDict({F:f, G:g, H:h}) | |
True | |
>>> d4 = BindingDict({F: f}) | |
>>> try: d4[F] = g | |
... except VariableBindingException as e: print(e) | |
Variable F already bound to another value | |
Test Unify | |
>>> try: f.unify(g, BindingDict()) | |
... except UnificationException as e: print(e) | |
... | |
Cannot unify f with g given {} | |
>>> f.unify(G, BindingDict()) == BindingDict({G: f}) | |
True | |
>>> try: f.unify(G, BindingDict({G: h})) | |
... except UnificationException as e: print(e) | |
... | |
Cannot unify f with G given {G: h} | |
>>> f.unify(G, BindingDict({G: f})) == BindingDict({G: f}) | |
True | |
>>> f.unify(G, BindingDict({H: f})) == BindingDict({G: f, H: f}) | |
True | |
>>> G.unify(f, BindingDict()) == BindingDict({G: f}) | |
True | |
>>> try: G.unify(f, BindingDict({G: h})) | |
... except UnificationException as e: print(e) | |
... | |
Cannot unify G with f given {G: h} | |
>>> G.unify(f, BindingDict({G: f})) == BindingDict({G: f}) | |
True | |
>>> G.unify(f, BindingDict({H: f})) == BindingDict({G: f, H: f}) | |
True | |
>>> G.unify(F, BindingDict()) == BindingDict({G: F}) | |
True | |
>>> try: G.unify(F, BindingDict({G: H})) | |
... except UnificationException as e: print(e) | |
... | |
Cannot unify G with F given {G: H} | |
>>> G.unify(F, BindingDict({G: F})) == BindingDict({G: F}) | |
True | |
>>> G.unify(F, BindingDict({H: F})) == BindingDict({G: F, H: F}) | |
True | |
Test Compile | |
>>> print(read_expr('g').compile_pos(Counter(), GlueFormula)) | |
(<ConstantExpression g>, []) | |
>>> print(read_expr('(g -o f)').compile_pos(Counter(), GlueFormula)) | |
(<ImpExpression (g -o f)>, []) | |
>>> print(read_expr('(g -o (h -o f))').compile_pos(Counter(), GlueFormula)) | |
(<ImpExpression (g -o (h -o f))>, []) | |
====================== | |
Glue | |
====================== | |
Demo of "John walks" | |
-------------------- | |
>>> john = GlueFormula("John", "g") | |
>>> print(john) | |
John : g | |
>>> walks = GlueFormula(r"\x.walks(x)", "(g -o f)") | |
>>> print(walks) | |
\x.walks(x) : (g -o f) | |
>>> print(walks.applyto(john)) | |
\x.walks(x)(John) : (g -o f)(g) | |
>>> print(walks.applyto(john).simplify()) | |
walks(John) : f | |
Demo of "A dog walks" | |
--------------------- | |
>>> a = GlueFormula("\\P Q.some x.(P(x) and Q(x))", "((gv -o gr) -o ((g -o G) -o G))") | |
>>> print(a) | |
\P Q.exists x.(P(x) & Q(x)) : ((gv -o gr) -o ((g -o G) -o G)) | |
>>> man = GlueFormula(r"\x.man(x)", "(gv -o gr)") | |
>>> print(man) | |
\x.man(x) : (gv -o gr) | |
>>> walks = GlueFormula(r"\x.walks(x)", "(g -o f)") | |
>>> print(walks) | |
\x.walks(x) : (g -o f) | |
>>> a_man = a.applyto(man) | |
>>> print(a_man.simplify()) | |
\Q.exists x.(man(x) & Q(x)) : ((g -o G) -o G) | |
>>> a_man_walks = a_man.applyto(walks) | |
>>> print(a_man_walks.simplify()) | |
exists x.(man(x) & walks(x)) : f | |
Demo of 'every girl chases a dog' | |
--------------------------------- | |
Individual words: | |
>>> every = GlueFormula("\\P Q.all x.(P(x) -> Q(x))", "((gv -o gr) -o ((g -o G) -o G))") | |
>>> print(every) | |
\P Q.all x.(P(x) -> Q(x)) : ((gv -o gr) -o ((g -o G) -o G)) | |
>>> girl = GlueFormula(r"\x.girl(x)", "(gv -o gr)") | |
>>> print(girl) | |
\x.girl(x) : (gv -o gr) | |
>>> chases = GlueFormula(r"\x y.chases(x,y)", "(g -o (h -o f))") | |
>>> print(chases) | |
\x y.chases(x,y) : (g -o (h -o f)) | |
>>> a = GlueFormula("\\P Q.some x.(P(x) and Q(x))", "((hv -o hr) -o ((h -o H) -o H))") | |
>>> print(a) | |
\P Q.exists x.(P(x) & Q(x)) : ((hv -o hr) -o ((h -o H) -o H)) | |
>>> dog = GlueFormula(r"\x.dog(x)", "(hv -o hr)") | |
>>> print(dog) | |
\x.dog(x) : (hv -o hr) | |
Noun Quantification can only be done one way: | |
>>> every_girl = every.applyto(girl) | |
>>> print(every_girl.simplify()) | |
\Q.all x.(girl(x) -> Q(x)) : ((g -o G) -o G) | |
>>> a_dog = a.applyto(dog) | |
>>> print(a_dog.simplify()) | |
\Q.exists x.(dog(x) & Q(x)) : ((h -o H) -o H) | |
The first reading is achieved by combining 'chases' with 'a dog' first. | |
Since 'a girl' requires something of the form '(h -o H)' we must | |
get rid of the 'g' in the glue of 'see'. We will do this with | |
the '-o elimination' rule. So, x1 will be our subject placeholder. | |
>>> xPrime = GlueFormula("x1", "g") | |
>>> print(xPrime) | |
x1 : g | |
>>> xPrime_chases = chases.applyto(xPrime) | |
>>> print(xPrime_chases.simplify()) | |
\y.chases(x1,y) : (h -o f) | |
>>> xPrime_chases_a_dog = a_dog.applyto(xPrime_chases) | |
>>> print(xPrime_chases_a_dog.simplify()) | |
exists x.(dog(x) & chases(x1,x)) : f | |
Now we can retract our subject placeholder using lambda-abstraction and | |
combine with the true subject. | |
>>> chases_a_dog = xPrime_chases_a_dog.lambda_abstract(xPrime) | |
>>> print(chases_a_dog.simplify()) | |
\x1.exists x.(dog(x) & chases(x1,x)) : (g -o f) | |
>>> every_girl_chases_a_dog = every_girl.applyto(chases_a_dog) | |
>>> r1 = every_girl_chases_a_dog.simplify() | |
>>> r2 = GlueFormula(r'all x.(girl(x) -> exists z1.(dog(z1) & chases(x,z1)))', 'f') | |
>>> r1 == r2 | |
True | |
The second reading is achieved by combining 'every girl' with 'chases' first. | |
>>> xPrime = GlueFormula("x1", "g") | |
>>> print(xPrime) | |
x1 : g | |
>>> xPrime_chases = chases.applyto(xPrime) | |
>>> print(xPrime_chases.simplify()) | |
\y.chases(x1,y) : (h -o f) | |
>>> yPrime = GlueFormula("x2", "h") | |
>>> print(yPrime) | |
x2 : h | |
>>> xPrime_chases_yPrime = xPrime_chases.applyto(yPrime) | |
>>> print(xPrime_chases_yPrime.simplify()) | |
chases(x1,x2) : f | |
>>> chases_yPrime = xPrime_chases_yPrime.lambda_abstract(xPrime) | |
>>> print(chases_yPrime.simplify()) | |
\x1.chases(x1,x2) : (g -o f) | |
>>> every_girl_chases_yPrime = every_girl.applyto(chases_yPrime) | |
>>> print(every_girl_chases_yPrime.simplify()) | |
all x.(girl(x) -> chases(x,x2)) : f | |
>>> every_girl_chases = every_girl_chases_yPrime.lambda_abstract(yPrime) | |
>>> print(every_girl_chases.simplify()) | |
\x2.all x.(girl(x) -> chases(x,x2)) : (h -o f) | |
>>> every_girl_chases_a_dog = a_dog.applyto(every_girl_chases) | |
>>> r1 = every_girl_chases_a_dog.simplify() | |
>>> r2 = GlueFormula(r'exists x.(dog(x) & all z2.(girl(z2) -> chases(z2,x)))', 'f') | |
>>> r1 == r2 | |
True | |
Compilation | |
----------- | |
>>> for cp in GlueFormula('m', '(b -o a)').compile(Counter()): print(cp) | |
m : (b -o a) : {1} | |
>>> for cp in GlueFormula('m', '((c -o b) -o a)').compile(Counter()): print(cp) | |
v1 : c : {1} | |
m : (b[1] -o a) : {2} | |
>>> for cp in GlueFormula('m', '((d -o (c -o b)) -o a)').compile(Counter()): print(cp) | |
v1 : c : {1} | |
v2 : d : {2} | |
m : (b[1, 2] -o a) : {3} | |
>>> for cp in GlueFormula('m', '((d -o e) -o ((c -o b) -o a))').compile(Counter()): print(cp) | |
v1 : d : {1} | |
v2 : c : {2} | |
m : (e[1] -o (b[2] -o a)) : {3} | |
>>> for cp in GlueFormula('m', '(((d -o c) -o b) -o a)').compile(Counter()): print(cp) | |
v1 : (d -o c) : {1} | |
m : (b[1] -o a) : {2} | |
>>> for cp in GlueFormula('m', '((((e -o d) -o c) -o b) -o a)').compile(Counter()): print(cp) | |
v1 : e : {1} | |
v2 : (d[1] -o c) : {2} | |
m : (b[2] -o a) : {3} | |
Demo of 'a man walks' using Compilation | |
--------------------------------------- | |
Premises | |
>>> a = GlueFormula('\\P Q.some x.(P(x) and Q(x))', '((gv -o gr) -o ((g -o G) -o G))') | |
>>> print(a) | |
\P Q.exists x.(P(x) & Q(x)) : ((gv -o gr) -o ((g -o G) -o G)) | |
>>> man = GlueFormula('\\x.man(x)', '(gv -o gr)') | |
>>> print(man) | |
\x.man(x) : (gv -o gr) | |
>>> walks = GlueFormula('\\x.walks(x)', '(g -o f)') | |
>>> print(walks) | |
\x.walks(x) : (g -o f) | |
Compiled Premises: | |
>>> counter = Counter() | |
>>> ahc = a.compile(counter) | |
>>> g1 = ahc[0] | |
>>> print(g1) | |
v1 : gv : {1} | |
>>> g2 = ahc[1] | |
>>> print(g2) | |
v2 : g : {2} | |
>>> g3 = ahc[2] | |
>>> print(g3) | |
\P Q.exists x.(P(x) & Q(x)) : (gr[1] -o (G[2] -o G)) : {3} | |
>>> g4 = man.compile(counter)[0] | |
>>> print(g4) | |
\x.man(x) : (gv -o gr) : {4} | |
>>> g5 = walks.compile(counter)[0] | |
>>> print(g5) | |
\x.walks(x) : (g -o f) : {5} | |
Derivation: | |
>>> g14 = g4.applyto(g1) | |
>>> print(g14.simplify()) | |
man(v1) : gr : {1, 4} | |
>>> g134 = g3.applyto(g14) | |
>>> print(g134.simplify()) | |
\Q.exists x.(man(x) & Q(x)) : (G[2] -o G) : {1, 3, 4} | |
>>> g25 = g5.applyto(g2) | |
>>> print(g25.simplify()) | |
walks(v2) : f : {2, 5} | |
>>> g12345 = g134.applyto(g25) | |
>>> print(g12345.simplify()) | |
exists x.(man(x) & walks(x)) : f : {1, 2, 3, 4, 5} | |
--------------------------------- | |
Dependency Graph to Glue Formulas | |
--------------------------------- | |
>>> from nltk.corpus.reader.dependency import DependencyGraph | |
>>> depgraph = DependencyGraph("""1 John _ NNP NNP _ 2 SUBJ _ _ | |
... 2 sees _ VB VB _ 0 ROOT _ _ | |
... 3 a _ ex_quant ex_quant _ 4 SPEC _ _ | |
... 4 dog _ NN NN _ 2 OBJ _ _ | |
... """) | |
>>> gfl = GlueDict('nltk:grammars/sample_grammars/glue.semtype').to_glueformula_list(depgraph) | |
>>> print(gfl) # doctest: +SKIP | |
[\x y.sees(x,y) : (f -o (i -o g)), | |
\x.dog(x) : (iv -o ir), | |
\P Q.exists x.(P(x) & Q(x)) : ((iv -o ir) -o ((i -o I3) -o I3)), | |
\P Q.exists x.(P(x) & Q(x)) : ((fv -o fr) -o ((f -o F4) -o F4)), | |
\x.John(x) : (fv -o fr)] | |
>>> glue = Glue() | |
>>> for r in sorted([r.simplify().normalize() for r in glue.get_readings(glue.gfl_to_compiled(gfl))], key=str): | |
... print(r) | |
exists z1.(John(z1) & exists z2.(dog(z2) & sees(z1,z2))) | |
exists z1.(dog(z1) & exists z2.(John(z2) & sees(z2,z1))) | |
----------------------------------- | |
Dependency Graph to LFG f-structure | |
----------------------------------- | |
>>> from nltk.sem.lfg import FStructure | |
>>> fstruct = FStructure.read_depgraph(depgraph) | |
>>> print(fstruct) # doctest: +SKIP | |
f:[pred 'sees' | |
obj h:[pred 'dog' | |
spec 'a'] | |
subj g:[pred 'John']] | |
>>> fstruct.to_depgraph().tree().pprint() | |
(sees (dog a) John) | |
--------------------------------- | |
LFG f-structure to Glue | |
--------------------------------- | |
>>> fstruct.to_glueformula_list(GlueDict('nltk:grammars/sample_grammars/glue.semtype')) # doctest: +SKIP | |
[\x y.sees(x,y) : (i -o (g -o f)), | |
\x.dog(x) : (gv -o gr), | |
\P Q.exists x.(P(x) & Q(x)) : ((gv -o gr) -o ((g -o G3) -o G3)), | |
\P Q.exists x.(P(x) & Q(x)) : ((iv -o ir) -o ((i -o I4) -o I4)), | |
\x.John(x) : (iv -o ir)] | |
.. see gluesemantics_malt.doctest for more | |